Inkjet printed hydrophobic microfluidic channelling on porous substrates - Koivunen, Risto; Jutila, Eveliina; Gane, Patrick (Journal of Print and Media Technology Research, 2023)
Paperfluidic devices consist of patterned microfluidic channels formed on paper or paper-like material. The direction of surface and bulk liquid flow is typically controlled by patterning hydrophobic barriers on the otherwise hydrophilic paper substrate. A variety of hydrophobic materials and functional printing methods can be used for the patterning. Unlike conventional graphical printing, hydrophobising ink must penetrate the whole depth of the substrate to form an effective barrier against leakage from the channel. This study focuses on the development of solvent-based hydrophobic inks for inkjet printing of microfluidic patterning. Hydrophobic inks were produced by dissolving alkyl ketene dimer (AKD) and polystyrene (PS) in p-xylene. Hydrophobic test patterns were inkjet printed with these inks on two highly porous filter papers. The AKD-based ink was found to produce effective hydrophobic barriers but suffered from poorly defined borders. The PS-based ink produced well defined borders, but could only penetrate the full depth of the substrate on one of the chosen papers. Adding PS to AKD ink improved jettability. Hydrophobic ink penetration into filter paper was found to take place as surface film flow over the skeletal fibre structure of the paper. Therefore, paper fibre surface properties and ink surface tension and viscosity are considered to play controlling roles in determining the penetration depth. Differences seen with respect to aqueous wicking behaviour at the interface/border between hydrophilic and hydrophobic regions might be due to the Marangoni derived coffee stain effect and likely to interactions with the fibre surfaces.